Pengaruh Brand Image Dan Harga Terhadap Keputusan Pembelian Pada Produk Iphone Di Outlet Ibox Bxc Tangerang Selatan - Pramana Hidayat, Geraldy; Dana Dana (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine the effect of Brand image and price on purchasing decisions of Iphone products in South Tangerang. The method used is quantitative with an approach to the relationship between variables, with data collection conducted using questionnaires. The population of this study consists of 31,950 residents of South Tangerang who visited one of the stores selling iPhones, and the sample was taken using Lemeshow's formula, resulting in 95.756 consumers, rounded up to 100 consumers. The data analysis methods used include descriptive analysis, instrument testing, classical assumption testing, simple and multiple linear regression, correlation coefficient testing, determination coefficient, as well as t-test and F-test using SPSS version 26. The study results indicate that Brand image (X1) has a significant effect on purchasing decisions (Y) with a regression test result of Ŷ = 0.499 + 1.462X1. The correlation coefficient value of 0.918 indicates a very strong relationship, with a determination coefficient of 84.3%, while the remaining 15.7% is influenced by other variables. The t-test shows that the calculated t-value (22.950) is greater than the table t-value (1.984) and the significance value (0.00) is less than 0.05, thus Ha1 is accepted and Ho1 is rejected. Price (X2) also has a significant effect on purchasing decisions (Y) with the regression test result Ŷ = 3.781 + 1.064X2. The correlation coefficient value of 0.929 indicates a very strong relationship, with a determination coefficient of 86.4%, while 13.6% is influenced by other variables. The t-test shows that the calculated t-value (24.902) is greater than the table t-value (1.984) and the significance value (0.00) is less than 0.05, thus Ha2 is accepted and Ho2 is rejected. Additionally, Brand Image (X1) and Price (X2) simultaneously also affect purchase decisions (Y), with the regression test result Ŷ = 1.437 + 0.593X1 + 0.661X2. The correlation coefficient value of 0.937 indicates a very strong relationship, with a determination coefficient of 87.8%, while 12.2% is influenced by other variables. The F test shows that the calculated F value (349.365) is greater than the table F value (3.09) and the Sig value (0.00) is less than 0.05, so Ha3 is accepted and Ho3 is rejected, which means that Brand image X1 & price X2 affect purchasing decisions Y Keywords: Brand Image, Price, Purchasing Decision